Genetic polymorphisms in MIR1208 and MIR5708 are associated with susceptibility to COPD in the Chinese population - Y. Zhou; F. Bai; X. Li; G. Zhou; X. Tian; G. Li; Y. Zhang; X. Zhou; D. Xu; Y. Ding (Pulmonology, 2023)
Background: Chronic obstructive pulmonary disease (COPD) is a complex disease characterized by limited airflow and is influenced by genetic and environmental factors. The purpose of this study was to investigate the effects of gene polymorphisms in MIR5708 and MIR1208 on COPD risk. Methods: Four single nucleotide polymorphisms (SNPs) in MIR5708 (rs6473227 and rs16907751) and MIR1208 (rs2608029 and rs13280095) were selected and genotyped among 315 COPD patients and 314 healthy controls using the Agena MassARRAY platform. SPSS 18.0 was used for statistical analysis and data processing. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to assess the association between genetic variants of MIR1208 and MIR5708 and COPD risk. Results: The results suggested that rs16907751 variants in MIR5708 contributed to an increased susceptibility to COPD in the allelic (P = 0.001), co-dominant (homozygous) (P = 0.001), dominant (P = 0.017), recessive (P = 0.002), and additive (P = 0.002) models. The effects of MIR5708 and MIR1208 gene polymorphisms on the risk of COPD were age-, sex-, smoking status-, and BMI-related. Furthermore, the C-A and G-A haplotypes of rs2608029 and rs13280095 in MIR1208 were identified as risk factors for COPD in the population over 70 years (P = 0.029) and in women (P = 0.049), respectively. Finally, significant associations between rs16907751genotypes with pulse rate and forced expiratory volume in 1 s were found among COPD patients. Conclusion: Genetic polymorphisms in MIR5708 and MIR1208 are associated with increased risk of COPD in China.